Alcohol Induced Toxic Optic Neuropathy- A Prospective Study - Kumar, Munish; Yadav, Vijay Kumar (Nepal Journal of Neuroscience, 2022)
Introduction: We report cases of methanol induced toxic optic neuropathy with their clinical and MRI brain findings.Methods: Prospective study of four consecutive cases presented between July to December 2021 at emergency department of Patna Medical College, Patna, India. Visual acuity and MRI brain findings noted in each case.Results: All the patients were males and chronic drinkers with history of consuming adulterated alcohol. All presented with altered consciousness, metabolic acidosis and almost complete painless visual loss bilaterally. MRI brain showed bilateral T2W hyperintansity in putamen and blooming on GRE suggestive of bilateral putaminal hemorrhagic necrosis. None of the patient had improvement after Intravenous methyprednisolone.Conclusion: Alcohol related toxic optic neuropathy is a serious disorder causing bilateral, almost complete visual loss. Typical MRI brain findings could point towards diagnosis.